Aplicação das cinzas de bagaço de cana-de-açúcar como material adsorvente na purificação de óleo residual - Bonassa, Gabriela (2018)
The sugarcane bagasse fly ash are byproducts generated in the sugar and alcohol industry in energy cogeneration, and due to their alkaline characteristics, abrasive and porous, present great potential to be used as an adsorbent material, such as in cooking oil purification. These residual oil are derived from the process of cooking food, presenting itself as an environmental, economic and social alternative for use as a feedstock for biodiesel production. By considering the high temperatures and multiples utilizations of these oils, which are put into contact with diversified and frozen foods, induce the minimization of their quality due to the high concentration of free fatty acids, moisture and peroxides arising from hydrolysis and oxidation reactions. In this sense, the aim of the present work was the evaluation of the adsorbent potential of sugarcane bagasse fly ash and activated carbon in the purification of waste cooking oil, evaluating operational conditions that may influence the adsorption process. Both materials were characterized by N2 Physisorption, Scanning Electron Microscopy and Dispersive Energy Spectroscopy, for textural, morphological and composition analyzes. In the waste cooking oil treatment step, temperatures rages from 15 to 25 ºC, adsorbent mass from 0,33 to 4,95 g and agitation speed between 50 and 200 rpm, the independent variables were predetermined in an experimental planning of the Rotational Central Composite Design, which aims to optimize the process by reducing the number of tests. It was found statistically in the intervals studied that the different conditions were statistically significant in the reduction of acidity (AV) and peroxide (PV) values and both materials provided near efficiencies in the improvement of residual oil quality, wherein the ashes led to a AV and PV minimizations around 59 and 25 %, respectively, while by using the commercial adsorbent (activated carbon), 57 and 27 %. The utilization of bagasse fly ashes in the waste cooking oil treatment, due to their low cost and be a waste generated in large quantities in Brazil provide positive advantages from the environmental, economic and social point of view. In addition, considering its efficiency to such application which is comparable to the commercial adsorbents, they minimize the expenses relates to the feedstock purification stages for biodiesel synthesis, from residual oils with high levels of oxidation and free fatty acids.